SOCIAL MEDIA USE IN MUNICIPALITIES IN LATVIA - Sloka, Biruta; Lase, Kate; Vītols, Mārcis (University of Zagreb, 2021)
Social media use in municipalities has expanded around the world on the basis of development of internet and technology. Although each social network offers substantial benefits and opportunities to municipalities, research of social media use in municipalities in Latvia remains scant. Purpose of the study is to analyse how much and which social media use municipalities in Latvia. Research methods used in preparation of the paper: recent scientific publication studies, analysis of social media of municipalities of Latvia, survey on social media use in municipalities in Latvia realized on April 2021. For data analysis there were used indicators of descriptive statistics: indicators of central tendency or location (arithmetic mean, mode, median, quartiles), indicators of variability (variance, standard deviation, standard error of mean), cross – tabulations, statistical tests of hypotheses and analysis of variance (ANOVA). Findings show that 13 of 119 municipalities of Latvia lack of social media. The results of the research can provide valuable pointers for decision makers how to improve social media administration in municipalities in Latvia.
Keywords: Digital marketing; Internet; municipalities; social media